2020
DOI: 10.25170/djm.v19i1.1184
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Tidur Yang Buruk Akibat Gangguan Makan Pada Pelajar Sekolah Menengah Di Jakarta

Abstract: Pendahuluan: Gangguan makan dapat memengaruhi kualitas tidur, terutama remaja karena masa remaja merupakan masa terjadi perubahan fisik dan psikologi. Pelepasan hormon dan metabolisme glukosa terjadi saat tidur, sedangkan nafsu makan dipengaruhi oleh sistem neuroendokrin. Tujuan penelitian ini adalah untuk mengetahui hubungan risiko gangguan makan terhadap kualitas tidur remaja karena remaja zaman sekarang kurang memedulikan waktu makan dan makanan yang dikonsumsi. Metode: Penelitian potong lintang dilak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…The association between emotional conditions and insomnia is consistent with the study by Susanti [25] which found that patients with poor sleep patterns have a relationship with the occurrence of distress and experience an increase in thinking load. The association between insomnia and loss of appetite is corroborated in the studies conducted by Julian and Kurniawan [26] and Vicario [27], which explained that the need for sleep and food are interconnected, and that a poor diet will lead to insomnia. The associations between loss of appetite and emotion, and between nausea and loss of appetite are in line with the observations of Ambarwati [23] and Rumastika and Surarso [28].…”
Section: Discussionmentioning
confidence: 62%
“…The association between emotional conditions and insomnia is consistent with the study by Susanti [25] which found that patients with poor sleep patterns have a relationship with the occurrence of distress and experience an increase in thinking load. The association between insomnia and loss of appetite is corroborated in the studies conducted by Julian and Kurniawan [26] and Vicario [27], which explained that the need for sleep and food are interconnected, and that a poor diet will lead to insomnia. The associations between loss of appetite and emotion, and between nausea and loss of appetite are in line with the observations of Ambarwati [23] and Rumastika and Surarso [28].…”
Section: Discussionmentioning
confidence: 62%
“…JNC http://jurnal.poltekkesgorontalo.ac.id/index.php/JNC/index dikatakan bahwa gangguan pangan adalah salah satu hal yang dapat memengaruhi tidur seseorang (Julian & Kurniawan, 2020). …”
unclassified